2020
DOI: 10.1115/1.4048080
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Recovery From Naturally Fractured Gas Reservoirs With Seismic Vibrations

Abstract: Water level rising in fracture networks of a naturally fractured gas reservoir is extremely challenging and can significantly decrease the ultimate recovery due to reservoir heterogeneity. Although capillary drainage and gravity force can enhance the displacement of gas recovery from matrix to fracture, these forces may not be so effective in mobilizing large amount of trapped gas through matrix. So called, the use of seismic wave can be suggested as a low cost and environmentally friendly enhanced method comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…When there is gas in the pores, the frequency dispersion and attenuation are the least obvious, and the speed dispersion and attenuation are only found in a very high frequency range; when there is oil, the medium has the most serious dispersion and attenuation, and the salt water comes next. Finally, the influence of the fracture density on the phase velocity and anisotropy parameters of the equivalent medium is analyzed, and it is found that the increase of the fracture density increases the dispersion and attenuation of the medium speed, the difference between the high and low frequency limits is large, and the increase of the medium to the opposite side (Zare et al 2020). Marlstones with higher shale content are not easy to form fractures, while pure marlstones are easy to form effective fractures under stress.…”
Section: Anisotropy Analysismentioning
confidence: 99%
“…When there is gas in the pores, the frequency dispersion and attenuation are the least obvious, and the speed dispersion and attenuation are only found in a very high frequency range; when there is oil, the medium has the most serious dispersion and attenuation, and the salt water comes next. Finally, the influence of the fracture density on the phase velocity and anisotropy parameters of the equivalent medium is analyzed, and it is found that the increase of the fracture density increases the dispersion and attenuation of the medium speed, the difference between the high and low frequency limits is large, and the increase of the medium to the opposite side (Zare et al 2020). Marlstones with higher shale content are not easy to form fractures, while pure marlstones are easy to form effective fractures under stress.…”
Section: Anisotropy Analysismentioning
confidence: 99%